2016
DOI: 10.1111/mec.13510
|View full text |Cite
|
Sign up to set email alerts
|

Host associations and beta diversity of fungal endophyte communities in New Guinea rainforest trees

Abstract: Processes shaping the distribution of foliar fungal endophyte species remain poorly understood. Despite increasing evidence that these cryptic fungal symbionts of plants mediate interactions with pathogens and herbivores, there remain basic questions regarding the extent to which dispersal limitation and host specificity might shape fungal endophyte community composition in rainforests. To assess the relative importance of spatial pattern and host specificity, we isolated fungi from a sample of mapped trees in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
110
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(132 citation statements)
references
References 97 publications
16
110
4
2
Order By: Relevance
“…Our finding that host identities are negligible in structuring sapling endophyte communities, while in stark contrast to studies on bacterial and fungal leaf epiphytes, support findings from fungal endophyte studies (e.g. Redford, Bowers, Knight, Linhart, & Fierer, ; Kembel et al, ; Laforest‐Lapointe et al, ; Suryanarayanan, Vankatesan, & Mirali, ; Suryanarayanan et al, ; Oono, Lefevre, & Lutzoni, ; Vincent, Weiblen, & May, ). Indeed, previous studies in temperate and tropical forests demonstrated that host species identity explained significant variation (27% to >50%) in epiphyte bacterial and fungal community composition (Kembel & Mueller, ; Kembel et al, ; Laforest‐Lapointe et al, ; Redford et al, ).…”
Section: Discussionsupporting
confidence: 86%
“…Our finding that host identities are negligible in structuring sapling endophyte communities, while in stark contrast to studies on bacterial and fungal leaf epiphytes, support findings from fungal endophyte studies (e.g. Redford, Bowers, Knight, Linhart, & Fierer, ; Kembel et al, ; Laforest‐Lapointe et al, ; Suryanarayanan, Vankatesan, & Mirali, ; Suryanarayanan et al, ; Oono, Lefevre, & Lutzoni, ; Vincent, Weiblen, & May, ). Indeed, previous studies in temperate and tropical forests demonstrated that host species identity explained significant variation (27% to >50%) in epiphyte bacterial and fungal community composition (Kembel & Mueller, ; Kembel et al, ; Laforest‐Lapointe et al, ; Redford et al, ).…”
Section: Discussionsupporting
confidence: 86%
“…Schulz, Boyle, Draeger, Rommert, and Krohn () found that approximately 80% of fungal endophyte species produce secondary compounds with antifungal activity, which mediated the competition among fungal species (Saunders et al, ). Previous studies have also indicated that different host species show distinct FEF assemblages (Higgins et al, ; Solis, Dela Cruz, Schnittler, & Unterseher, ; Vincent, Weiblen, & May, ). An early study of FEF assemblages on coniferous trees found that many endophytes were restricted to a single or a restricted number of host species (Carroll & Carroll, ).…”
Section: Introductionmentioning
confidence: 91%
“…, Vincent et al. ). Therefore, a similar relationship between plant and fungal diversity could be expected.…”
Section: Introductionmentioning
confidence: 99%